Effect Of Compensation, Workload And Organizational Support On Employee Performance At Super Dazzle Yogyakarta: inggris - Mahfuddin Mahfuddin; Ignatius Soni Kurniawan; Eko Yulianto Yulianto (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the influence of compensation, workload, and organizational support on employee performance at Super Dazzle Yogyakarta. This research is important considering that employee performance is a major factor in the success of a retail company. Methodology: The approach used is quantitative with associative research. The population in this study were all Super Dazzle Yogyakarta employees, with a sample of 102 respondents determined using saturated sampling techniques. Data were collected through directly distributed questionnaires and analyzed using multiple linear regression. Results: The results showed that compensation and organizational support had a positive and significant effect on employee performance, while workload had a negative and significant effect on employee performance. Findings: These findings indicate that a fair compensation system, adequate organizational support, and appropriate workload management are key factors in improving employee performance. Novelty & Originality: The novelty of this study lies in the simultaneous testing of these three variables in the context of a local retail company, which is still relatively rarely studied. This study is important because it provides empirical evidence on how compensation, workload, and organizational support jointly influence employee performance in a local retail context, offering practical insights for human resource management decision-making in similar service-based organizations. Conclusions: The results show that improved employee performance can be achieved through a balance between providing good compensation, strong organizational support, and proportional workload control to support the achievement of company goals. Type of Paper: This paper is an empirical research paper.